2014
DOI: 10.20286/jech-010119
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Consumption of Fast Foods Among Women Based on the Social Cognitive Theory

Abstract: Introduction: Fast-food consumption among Iranian families appears to be increasing probably due to urbanization, popularization of western-style diets and increased women's labor force participation. Few theory-based investigations have assessed the determinants of fast food consumption. Therefore, the aim of this study was to determine the predictors of fast food consumption, based on the social cognitive theory (SCT) among women referred to health centers in Hamadan, Western of Iran. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…It increased the mean score of value expectations in the intervention group. These findings were consistent with the results of the study by Beiranvandpour (13). Outcome expectancy is another aspect of SCT investigated in the current study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It increased the mean score of value expectations in the intervention group. These findings were consistent with the results of the study by Beiranvandpour (13). Outcome expectancy is another aspect of SCT investigated in the current study.…”
Section: Discussionsupporting
confidence: 94%
“…data collection tools used in the current study were students' demographic information including age, weight, height, mother's education and occupation, father's occupation, household aspect, and economic status. To evaluate fast food consumption rate and SCT aspects, the Beiranvandpour questionnaire including fast food consumption frequency in the past week (8 items), nutritional knowledge (5 items), value expectancy (8 items), outcome expectancy (8 items), and self-efficacy (7 items) was used (13).…”
Section: Methodsmentioning
confidence: 99%
“…Based on this theory, changes in behavior are affected from the complex interaction that called "reciprocal determinism", which happens between individual, environmental factors and especial characteristics of a behavior. This theory has been successfully employed in various nutritional behaviors such as eating snacks (22,23), fast food (24,25), and breakfast (16,26). For example, studies of Salimi et al, showed that variables of this theory could explain 64% of the variance of eating breakfast among female students.…”
Section: Introductionmentioning
confidence: 99%